Effect of different immunosuppressive therapies on the lipid pattern in kidney-transplanted rats - Lausada, Natalia Raquel (2005)
We analyzed the effect of oral administration of cyclosporine- methylprednisone (CsA-MP) and sirolimus (SRL) on the lipid pattern of kidney-transplanted rats after a 7-day survival. A significant increase in plasma cholesterol in CsA-MP group (control: 26 ± 3 mg/dl vs. 59 ± 8 mg/dl, P < 0.05) and in triglyceride levels in SRL group (control: 53 ± 4 mg/dl vs. 114 ± 3 mg/dl, P < 0.05), was shown. Kidney microsomal membranes from both treated groups showed that cholesterol and triglyceride values and the relative percentage of arachidonic acid in the total amount of n-6 fatty acids decreased. A diminution of linoleic acid occurred in testis (control: 9.4 ± 0.1 mg/dl vs. CsA-MP: 6.0 ± 0.3 mg/dl and vs. SRL: 6.8 ± 0.2 mg/dl, P < 0.05), liver (control: 17.7 ± 0.6 mg/dl vs. CsA-MP: 15.1 ± 0.6 mg/dl and SRL: 13.5 ± 0.8 mg/dl, P < 0.05) and erythrocyte membranes (control:11.7 ± 0.1% vs. CsA-MP: 10.6 ± 0.2% and SRL: 10.0 ± 0.4%, P < 0.01). The immunosuppressive therapies improved the rejection rate of the graft, fact that was remarkable in the SRL-treated group. However, lipid abnormalities still remain in spite of immunosuppressive therapies. (150).